Modeling the relationship between the structure and melting point of pyrazolone derivatives: topological approach - M. I. Skvortsova; N. S. Rukk (Тонкие химические технологии)
In the framework of the statistical approach the non-linear «structure - melting point» model for pyrazolone derivatives is constructed. Number of topological parameters calculated from the structural formula was used for the quantitative description of the molecular structure. The results of calculation of the melting points for a series of compounds of considered class are reported.